Is there any transfer between countermovement jump and swimming track start performance? - Carvalho, D. D.; Fonseca, P.; Marinho, D. A.; Silva, A. J.; Zacca, R.; Mourão, L.; Fernandes, R. J.; Vilas-Boas, J. P. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to determine if the countermovement jump could predict swimming starts performance. Ten elite swimmers performed one maximal countermovement jump on an extensometric force platform and three maximal track start on an instrumented starting block. Results showed an inverse relationship between 15 m starting time and jump variables (r = -0.86, -0.64 and -0.92 for jump height, peak vertical force and peak power, respectively; p < 0.05) and no significant correlation between relative peak vertical force and start variables. Regression equation for 15 m time prediction was defined by jump height and peak vertical force (r = 0.890, adjusted r2 = 0.734). In addition, results suggest that swimmers with higher jumps and higher peak vertical force are faster on the 15m mark when using a track start.